Evaluation of targeted and untargeted effects-based monitoring tools to assess impacts of contaminants of emerging concern on fish in the South Platte River, CO. (August 2018) - Ekman, Drew R.; Keteles, Kristen; Beihoffer, Jon; Cavallin, Jenna E.; Dahlin, Kenneth; Davis, John M.; Jastrow, Aaron; Lazorchak, James M.; Mills, Marc A.; Murphy, Mark; Nguyen, David; Vajda, Alan M.; et al.
Abstract: Rivers in the arid Western United States face increasing influences from anthropogenic contaminants due to population growth, urbanization, and drought. To better understand and more effectively track the impacts of these contaminants, biologically-based monitoring tools are increasingly being used to complement routine chemical monitoring. This study was initiated to assess the ability of both targeted and untargeted biologically-based monitoring tools to discriminate impacts of two adjacent wastewater treatment plants (WWTPs) on Colorado's South Platte River. A cell-based estrogen assay ( in vitro, targeted) determined that water samples collected downstream of the larger of the two WWTPs displayed considerable estrogenic activity in its two separate effluent streams. Hepatic vitellogenin mRNA expression ( in vivo, targeted) and NMR-based metabolomic analyses ( in vivo, untargeted) from caged male fathead minnows also suggested estrogenic activity downstream of the larger WWTP, but detected significant differences in responses from its two effluent streams. The metabolomic results suggested that these differences were associated with oxidative stress levels. Finally, partial least squares regression was used to explore linkages between the metabolomics responses and the chemical contaminants that were detected at the sites. This analysis, along with univariate statistical approaches, identified significant covariance between the biological endpoints and estrone concentrations, suggesting the importance of this contaminant and recommending increased focus on its presence in the environment. These results underscore the benefits of a combined targeted and untargeted biologically-based monitoring strategy when used alongside contaminant monitoring to more effectively assess ecological impacts of exposures to complex mixtures in surface waters. Graphical abstract: Image 1 Highlights: In vitro and in vivo effects-based monitoring tools provide complementary findings. Field-based metabolomics can discriminate separate effluent streams. Untargeted metabolomics can detect effects not captured by targeted techniques. Covariance of estrone with biological responses recommends increased monitoring. Abstract : The use of a combined targeted and untargeted effects-based monitoring approach is critical when evaluating biological responses in fish exposed to complex mixtures of contaminants.